O movimento identitário de gestores de escolas inovadoras da cidade de São Paulo: investigação e ensinamentos para a sua formação - Santos, Alcielle dos (2021)
Meaningful changes or even transformations in Education demand different analysis dimensions. In this thesis it is considered the need of implementing new school models, that fit the 21st century needs. So, this research had as objective investigate and understand the pedagogical managers’ identity, considering everyone from the school and its expansion within specific territories. These managers were principals in three innovative schools in the city of São Paulo, and they were studied according to their training and professionalism, and management processes. The polysemy of the term innovation is brought up since the introduction, to contextualize the choice for the term “educational innovation”, and the basis was the Ministry of Education's Initiative for Innovation and Creativity in 2015 (management, curriculum, environment, methodology, and intersectoriality). The research used the qualitative approach as a study that had the observation, the participant observation, and the action research. The scenery of each one of the schools where the said managers acted was detailed from documentary research and field observations. Besides these methodologic choices, for the study of the pedagogical managers’ identity, semi-structured interviews were carried out. The pedagogical managers’ identity was approached from Dubar (2005; 2009), and Placco (2008; 2010) was also considered. As theoretical frameworks of analysis, the Sociology of Translation by Callon (1980) and Latour (2000) and the Complex Thought by Morin (2013) were used. The school management paths were considered according to management, curriculum, environment, methodology, and intersectoriality, criteria from the Ministry of Education's Initiative, addressed in dialogue with authors as Carbonell (2002), Singer (2017; 2018; 2019), Ghanem Júnior (2013), and Tavares (2019; 2020), that consider the educational innovation at school. The analysis of the data, based on the theoretical references, presents an answer to the central question: what is the relationship between innovation and the pedagogical managers’ identity of these processes and what characterizes it? As a result, we could verify that the actions of the pedagogical managers as innovation translators were essential to everyone from the school, who had their schools as references. We observed there was a great potential for territorial expansion, starting from the intersectoriality with other social facilities in the areas of education, culture, health, and social assistance in the neighborhoods where those schools are located, so that they can stimulate other educational innovation processes. So, we consider essential the investigation of successful practices, from the management’s point of view, as experiences that bring teachings to other networks. Finally, we propose these actions should be supported by Public Policies that recognize them as innovative experiences and exploit their managers’ training and leadership potential, the ones who translated different logics into common statements, which made innovation in their schools possible